Marginal propensity to save in China : a dynamic panel analysis on provincial data - Tan, April Shu Ying (2008)
In this paper, a dynamic panel analysis was conducted on the determinants of urban household savings rate in China. Panel data on Chinese provinces for the period 1995-2005 is divided broadly into three regions, namely inland, coastal and western. The paper consists of 2 main findings. Empirical results showed that China’s marginal propensity to save (MPS) has been rising and the magnitude of rise in MPS is estimated. Also, determinants that affect MPS were identified and it was concluded that share of expenditure on healthcare, residence and education contributed to the increase in MPS.